2007
DOI: 10.1136/oem.2006.029223
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of cancer mortality and incidence among dentists

Abstract: This review assesses the epidemiological literature describing dentist mortality and cancer incidence risk. In the dental workplace a variety of hazards may have been historically present or currently exist which can impact dentists' long-term health, including their mortality and cancer incidence. The epidemiological literature of dentistry's health outcomes was reviewed with a focus on all cancers combined and cancers of the brain, lung, reproductive organs and skin. Relevant studies were identified using ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Several studies have reported numerous determinants or risk factors for a variety of occupational diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, none of these studies were based on quantitative research or were designed to investigate discriminating factors between cases (e.g.…”
mentioning
confidence: 98%
“…Several studies have reported numerous determinants or risk factors for a variety of occupational diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, none of these studies were based on quantitative research or were designed to investigate discriminating factors between cases (e.g.…”
mentioning
confidence: 98%
“…Even when professionals of both genders perform identical job tasks, with similar external exposures, the absorbed dose may be higher among men as a consequence of their larger surface area, which provides more opportunity for dermal absorption. Altogether, this scenario of continuous exposure to several risk factors for decades of activity in the dentistry practice may create conditions that are favorable for carcinogenesis [Simning and van Wijngaarden, 2007]. However, women have thinner skin in many areas of the body, a smaller volume of total body water, and a higher percentage of body fat, which can allow easier penetration, absorption, and storage of chemicals [Silvaggio and Mattison, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Increased risks have also been reported, albeit inconsistently, for farming occupations [ 110 , 118 ], textile and clothing workers [ 89 , 107 ], leather and fur processors and glass-manufacturing workers [ 110 ], nurses [ 60 ], dentists [ 164 ], electricity power plant workers [ 165 ], semiconductor and computer manufacturing industries [ 102 , 125 ], metalworking and automotive plastics manufacturing [ 166 ], and scientists [ 126 ]. However, similar occupations have also been associated with absence of risk, for example, the occupation of farm worker [ 107 , 167 , 168 ], garment worker [ 119 ], glass manufacturer [ 106 ], dentist [ 164 ], and cosmetologist and manicurist [ 127 ].…”
Section: Specifi C Job Titlesmentioning
confidence: 95%
“…However, similar occupations have also been associated with absence of risk, for example, the occupation of farm worker [ 107 , 167 , 168 ], garment worker [ 119 ], glass manufacturer [ 106 ], dentist [ 164 ], and cosmetologist and manicurist [ 127 ].…”
Section: Specifi C Job Titlesmentioning
confidence: 99%